Profesionalisasi dan Pemberdayaan Guru dalam Konteks Peningkatan Mutu Pendidikan Nasional - Suyono Suyono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
Professionalism and empowerment of teachers are essential in improving the quality of the national education. As supported by many research findings, teachers are determining factors in students’ achievement. This article proposes ways of developing teacher professionalism by integrating the programs in teacher education and the supervision of teachers through the establishment of Teacher Quality Certification, which periodically evaluates teacher performance. This implies that teachers should be appointed on the basis of an agreed term, not on a life-long term as implemented in the current system.